Epilepsy Surgery for Tuberous Sclerosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
The surgical amenability of epileptogenic lesions in tuberous sclerosis complex is reviewed in the light of novel presurgical assessment in a report by investigators at University of Rome, Italy; Stanford University, Palo Alto, CA; and Central Illinois Neurohealth Sciences, Bloomington, IL, USA.